The Effect Of Good Dairy Farming Implementation On The Income Level And Efficiency Of Dairy Cows Farmers Businesses In West Malang Regency - Nadya Aulia Eka Wahyuni (ASTEEC, 2024)
The research aims to identify the implementation of Good Dairy Farming Practice, measure the income and efficiency of livestock business. The research was conducted in West Malang Regency from November 2021 to February 2022 in three sub-districts namely Pujon, Ngantang and Kasembon. Samples were taken as many as 100 using purposive sampling method. Data analysis was descriptive quantitative to identify the Good Dairy Farming Practice score, analysis of business efficiency with Cobb Douglass Production Function Regression, analysis of business income and influential factors with Multiple Linear Regression. The results showed that the application of GDFP with sufficient score categories is health aspects (2.84), milking hygiene aspects (2.76), feed nutrition and drinking water aspects (2.43), animal welfare aspects (2.87), environmental aspects (2.64), and unfavorable score category is socio-economic aspects (1.37). The average income of dairy farmers is IDR 70,959,024 per year. The results of income regression analysis showed that the variables of health and nutrition aspects had a very significant effect, the milking hygiene aspect had a significant effect, and the environmental aspect had a less significant effect. The results of the efficiency of the use of factors of milk production with a value of 1.215 showed increasing returns to scale. All aspects of GDFP are in the sufficient category and the socio-economic aspects are in the unfavorable category. This makes the farmer's income less than optimal.